Phylogenetic Patterns Suggest Broad Susceptibility to Chronic Wasting Disease Across Cervidae - Jonathan R. Mawdsley (Wildlife Society Bulletin, 2020)
ABSTRACT Chronic wasting disease presents significant management challenges for North American species of Cervidae, but susceptibility of other cervid taxa worldwide to this disease is largely unknown. A review of 7 published partial phylogenies for Cervidae indicates that known susceptible taxa are broadly distributed across each of these phylogenies, suggesting that there may be broad susceptibility to the disease within the family. Taxa particularly at risk based on phylogenetic and geographic proximity to known susceptible species include species of the genus Mazama in Central and South America and species of the genera Cervus and Rusa in Europe and Asia. © 2020 The Wildlife Society.